Screening macrocyclic peptide libraries by yeast display allows control of selection process and affinity ranking - Sara Linciano; Ylenia Mazzocato; Zhanna Romanyuk; Filippo Vascon; Lluc Farrera-Soler; Edward Will; Yuyu Xing; Shiyu Chen; Yoichi Kumada; Marta Simeoni; Alessandro Scarso; Laura Cendron; et al. (Nature Communications)
Abstract Macrocyclic peptides represent an attractive drug modality due to their favourable properties and amenability to in vitro evolution techniques such as phage or mRNA display. Although very powerful, these technologies are not without limitations. In this work, we address some of their drawbacks by developing a yeast display-based strategy to generate, screen and characterise structurally diverse disulfide-cyclised peptides. The use of quantitative flow cytometry enables real-time monitoring of the screening of millions of individual macrocyclic peptides, leading to the identification of ligands with good binding properties to five different protein targets. X-ray analysis of a selected ligand in complex with its target reveals optimal shape complementarity and extensive surface interaction, explaining its exquisite affinity and selectivity. The yeast display-based approach described here offers a facile, quantitative and cost-effective alternative to rapidly and efficiently discover and characterise genetically encoded macrocyclic peptide ligands with sufficiently good binding properties against therapeutically relevant targets.